Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve for [tex]\( X \)[/tex] in the matrix equation [tex]\( A \cdot X + B = C \)[/tex], we can follow these steps:
1. Rearrange the Equation:
First, we need to isolate [tex]\( A \cdot X \)[/tex]. So, we rearrange the equation as follows:
[tex]\[ A \cdot X = C - B \][/tex]
2. Calculate [tex]\( C - B \)[/tex]:
We need to subtract matrix [tex]\( B \)[/tex] from matrix [tex]\( C \)[/tex]:
[tex]\[ C = \begin{pmatrix} -42 & -20 \\ 5 & 4 \end{pmatrix} \][/tex]
[tex]\[ B = \begin{pmatrix} -7 & -9 \\ 4 & -1 \end{pmatrix} \][/tex]
[tex]\[ C - B = \begin{pmatrix} -42 & -20 \\ 5 & 4 \end{pmatrix} - \begin{pmatrix} -7 & -9 \\ 4 & -1 \end{pmatrix} = \begin{pmatrix} -42 - (-7) & -20 - (-9) \\ 5 - 4 & 4 - (-1) \end{pmatrix} = \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
So,
[tex]\[ C - B = \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
3. Solve for [tex]\( X \)[/tex] Using the Inverse of [tex]\( A \)[/tex]:
To solve for [tex]\( X \)[/tex], we need to multiply both sides of [tex]\( A \cdot X = C - B \)[/tex] by the inverse of [tex]\( A \)[/tex] (denoted as [tex]\( A^{-1} \)[/tex]):
[tex]\[ X = A^{-1} \cdot (C - B) \][/tex]
4. Calculate the Inverse of [tex]\( A \)[/tex]:
First, let's find the inverse of matrix [tex]\( A \)[/tex]:
[tex]\[ A = \begin{pmatrix} -3 & -4 \\ 1 & 0 \end{pmatrix} \][/tex]
The inverse of [tex]\( A \)[/tex], denoted by [tex]\( A^{-1} \)[/tex], is given by:
[tex]\[ A^{-1} = \frac{1}{\text{det}(A)} \cdot \text{adj}(A) \][/tex]
where [tex]\(\text{det}(A)\)[/tex] is the determinant of [tex]\( A \)[/tex] and [tex]\(\text{adj}(A)\)[/tex] is the adjugate of [tex]\( A \)[/tex].
The determinant of [tex]\( A \)[/tex] is:
[tex]\[ \text{det}(A) = (-3)(0) - (1)(-4) = 4 \][/tex]
The adjugate of [tex]\( A \)[/tex] is:
[tex]\[ \text{adj}(A) = \begin{pmatrix} 0 & -1 \\ 4 & -3 \end{pmatrix}^{\top} = \begin{pmatrix} 0 & 4 \\ -1 & -3 \end{pmatrix} \][/tex]
Thus,
[tex]\[ A^{-1} = \frac{1}{4} \cdot \begin{pmatrix} 0 & 4 \\ -1 & -3 \end{pmatrix} = \begin{pmatrix} 0 & 1 \\ -0.25 & -0.75 \end{pmatrix} \][/tex]
5. Multiply [tex]\( A^{-1} \)[/tex] by [tex]\( C - B \)[/tex]:
Now, we calculate [tex]\( X \)[/tex]:
[tex]\[ X = A^{-1} \cdot (C - B) = \begin{pmatrix} 0 & 1 \\ -0.25 & -0.75 \end{pmatrix} \cdot \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
We perform the matrix multiplication:
[tex]\[ X = \begin{pmatrix} 0 \cdot (-35) + 1 \cdot 1 & 0 \cdot (-11) + 1 \cdot 5 \\ -0.25 \cdot (-35) + -0.75 \cdot 1 & -0.25 \cdot (-11) + -0.75 \cdot 5 \end{pmatrix} = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
Therefore, the value of [tex]\( X \)[/tex] is:
[tex]\[ X = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
1. Rearrange the Equation:
First, we need to isolate [tex]\( A \cdot X \)[/tex]. So, we rearrange the equation as follows:
[tex]\[ A \cdot X = C - B \][/tex]
2. Calculate [tex]\( C - B \)[/tex]:
We need to subtract matrix [tex]\( B \)[/tex] from matrix [tex]\( C \)[/tex]:
[tex]\[ C = \begin{pmatrix} -42 & -20 \\ 5 & 4 \end{pmatrix} \][/tex]
[tex]\[ B = \begin{pmatrix} -7 & -9 \\ 4 & -1 \end{pmatrix} \][/tex]
[tex]\[ C - B = \begin{pmatrix} -42 & -20 \\ 5 & 4 \end{pmatrix} - \begin{pmatrix} -7 & -9 \\ 4 & -1 \end{pmatrix} = \begin{pmatrix} -42 - (-7) & -20 - (-9) \\ 5 - 4 & 4 - (-1) \end{pmatrix} = \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
So,
[tex]\[ C - B = \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
3. Solve for [tex]\( X \)[/tex] Using the Inverse of [tex]\( A \)[/tex]:
To solve for [tex]\( X \)[/tex], we need to multiply both sides of [tex]\( A \cdot X = C - B \)[/tex] by the inverse of [tex]\( A \)[/tex] (denoted as [tex]\( A^{-1} \)[/tex]):
[tex]\[ X = A^{-1} \cdot (C - B) \][/tex]
4. Calculate the Inverse of [tex]\( A \)[/tex]:
First, let's find the inverse of matrix [tex]\( A \)[/tex]:
[tex]\[ A = \begin{pmatrix} -3 & -4 \\ 1 & 0 \end{pmatrix} \][/tex]
The inverse of [tex]\( A \)[/tex], denoted by [tex]\( A^{-1} \)[/tex], is given by:
[tex]\[ A^{-1} = \frac{1}{\text{det}(A)} \cdot \text{adj}(A) \][/tex]
where [tex]\(\text{det}(A)\)[/tex] is the determinant of [tex]\( A \)[/tex] and [tex]\(\text{adj}(A)\)[/tex] is the adjugate of [tex]\( A \)[/tex].
The determinant of [tex]\( A \)[/tex] is:
[tex]\[ \text{det}(A) = (-3)(0) - (1)(-4) = 4 \][/tex]
The adjugate of [tex]\( A \)[/tex] is:
[tex]\[ \text{adj}(A) = \begin{pmatrix} 0 & -1 \\ 4 & -3 \end{pmatrix}^{\top} = \begin{pmatrix} 0 & 4 \\ -1 & -3 \end{pmatrix} \][/tex]
Thus,
[tex]\[ A^{-1} = \frac{1}{4} \cdot \begin{pmatrix} 0 & 4 \\ -1 & -3 \end{pmatrix} = \begin{pmatrix} 0 & 1 \\ -0.25 & -0.75 \end{pmatrix} \][/tex]
5. Multiply [tex]\( A^{-1} \)[/tex] by [tex]\( C - B \)[/tex]:
Now, we calculate [tex]\( X \)[/tex]:
[tex]\[ X = A^{-1} \cdot (C - B) = \begin{pmatrix} 0 & 1 \\ -0.25 & -0.75 \end{pmatrix} \cdot \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
We perform the matrix multiplication:
[tex]\[ X = \begin{pmatrix} 0 \cdot (-35) + 1 \cdot 1 & 0 \cdot (-11) + 1 \cdot 5 \\ -0.25 \cdot (-35) + -0.75 \cdot 1 & -0.25 \cdot (-11) + -0.75 \cdot 5 \end{pmatrix} = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
Therefore, the value of [tex]\( X \)[/tex] is:
[tex]\[ X = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.